2021
DOI: 10.1111/hae.14282
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of physical activity in people with haemophilia and its relationship with bleeding phenotype and treatment regimen

Abstract: Introduction Although the measurement of physical activity (PA) amongst people with haemophilia (PWH) has become increasingly widespread in recent years, the relationship between PA and bleeding phenotype remains poorly understood. In addition, the influence of various treatment regimens on this relationship has not been defined. Aim This review aimed to systematically assess the data that are available regarding PA levels amongst PWH, as well as the relationship between PA and bleeding. Methods A systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 62 publications
(763 reference statements)
1
24
0
Order By: Relevance
“…These findings were not unexpected, given that other efforts to use global hemostatic assays to predict the therapeutic requirements of SHA patients have been unsuccessful 50–52 . This may be attributed to an assortment of non‐exclusive factors, which include: (1) at low TF levels, even those SHA samples with the strongest relative hemostatic activity in CAT and TEG assays were still weak relative to normal donor samples, and thus indicated ineffective FVIII‐mediated hemostasis in vivo ; (2) all the patients in our cohort received rFVIII replacement therapy, which ensured they spent little or no time at the baseline levels of hemostatic function we assessed via CAT and TEG assays; (3) like many studies, ours was insufficiently powered to detect subtle relationships between hemostasis assay results and clinical parameters; and (4) key clinical outcomes such as joint bleeds are affected by many factors that show significant variation among patients and can act in combination, including patient physical activity, 53 body mass index, 54 and factor clearance rates 55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were not unexpected, given that other efforts to use global hemostatic assays to predict the therapeutic requirements of SHA patients have been unsuccessful 50–52 . This may be attributed to an assortment of non‐exclusive factors, which include: (1) at low TF levels, even those SHA samples with the strongest relative hemostatic activity in CAT and TEG assays were still weak relative to normal donor samples, and thus indicated ineffective FVIII‐mediated hemostasis in vivo ; (2) all the patients in our cohort received rFVIII replacement therapy, which ensured they spent little or no time at the baseline levels of hemostatic function we assessed via CAT and TEG assays; (3) like many studies, ours was insufficiently powered to detect subtle relationships between hemostasis assay results and clinical parameters; and (4) key clinical outcomes such as joint bleeds are affected by many factors that show significant variation among patients and can act in combination, including patient physical activity, 53 body mass index, 54 and factor clearance rates 55 …”
Section: Discussionmentioning
confidence: 99%
“…) key clinical outcomes such as joint bleeds are affected by many factors that show significant variation among patients and can act in combination, including patient physical activity,53 body mass index,…”
mentioning
confidence: 99%
“…According to Buxbaum et al, in the current social environment and with medical support, patients with hemophilia can be as physically active as their normal peers ( 16 ). A recent systematic review showed that physical activity levels varied greatly among heterogeneous samples of patients with hemophilia ( 4 ). In this study, patients participated in at least one physical activity besides routine walking.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread prophylaxis, physical activity levels of patients with hemophilia have increased ( 4 ). With appropriate FVIII level, the benefits of physical activity outweigh the risk of bleeding ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This idea coincides with the review by Lobet et al, which states that physical therapy has an essential role in combination with other new treatments in people with hemophilia, especially in their musculoskeletal complications [ 34 ]. In hemophilia management, the physiotherapist plays an important role in patient education and physical training, given that exercise can be helpful for them [ 35 ]. Moreover, physical therapy educational programs can reach higher patient satisfaction compared to physical therapy alone in patients at both a chronic and an acute phase [ 36 ].…”
Section: Discussionmentioning
confidence: 99%